Bias-scanning based tunable LSPR sensor. Issue 4 (8th January 2018) - Ran, Lingling; Tao, Yifei; Guo, Kai; Shen, Fei; Zhou, Hongping; Sun, Yongxuan; Zhang, Renbin; Zhou, Qingfeng; Yang, Jiuru; Yin, Zhiping; Guo, Zhongyi
Abstract : The principle and the characteristics of the bias-scanning based tunable localized surface plasmon resonance (LSPR) sensors for environmental refractive index have been theoretically and numerically investigated in detail. Abstract : The principle and the characteristics of the bias-scanning based tunable localized surface plasmon resonance (LSPR) sensors for environmental refractive index have been theoretically and numerically investigated in detail. The sensors exhibit linear negative-shifts in the scattering-bias spectral position when the refractive index of the surrounding medium increases. By bias-scanning, a single-wavelength measurement for sensing the environmental refractive index can be realized effectively. In addition, we demonstrate that the sensing performance of the designed sensor can be adjusted by nano-scale manipulations of metal nanoparticles' sizes and shapes. The proposed devices may pave the way for the development of electrochemical sensors that can convert spectrum scanning into bias scanning.